The heart communicates with the kidney exclusively through the guanylyl cyclase-A receptor: acute handling of sodium and water in response to volume expansion. - Kishimoto, I (1996)
Disruption of guanylyl cyclase-A (GC-A) results in mice displaying an elevated blood pressure, which is not altered by high or low dietary salt. However, atrial natriuretic peptide (ANP), a proposed ligand for GC-A, has been suggested as critical for the maintenance of normal blood pressure during high salt intake. In this report, we show that infusion of ANP results in substantial natriuresis and diuresis in wild-type mice but fails to cause significant changes in sodium excretion or urine output in GC-A-deficient mice. ANP, therefore, appears to signal through GC-A in the kidney. Other natriuretic/diuretic factors could be released from the heart. Therefore, acute volume expansion was used as a means to cause release of granules from the atrium of the heart. That granule release occurred was confirmed by measurements of plasma ANP concentrations, which were markedly elevated in both wild-type and GC-A-null mice. After volume expansion, urine output as well as urinary sodium and cyclic GMP excretion increased rapidly and markedly in wild-type mice, but the rapid increases were abolished in GC-A-deficient animals. These results strongly suggest that natriuretic/diuretic factors released from the heart function exclusively through GC-A.